Implementation of The Weighted Product Method for The Distribution of Bidik Misi Scholarships for Vacation High School Taruna Persada Dumai - Devit Satria (Jurnal Mantik, 2021)
Scholarship is one the factors that can increase student motivation. This scholarship is given to high achieving students and underprivileged students to continue to achieve their dreams. However, the low capacity of the scholarship means that this scholarship is very limited and is only for students who are eligible to receive it. However, it is not uncommon for errors to occur in distributing scholarships because there is no real calculation in the selection of scholarship acceptance so that the scholarships are not on target. Based on these problems, a decision support system that is able to solve the problem is needed so that the awarding of scholarships becomes more precise and efficient so that the authors conduct research using the Weighted Product method which can solve the problem by multiplying to connect the attribute value, where the attribute value must first be ranked by weight. attribute in question. As for the criteria for providing scholarships, namely achievements, parents' income, number of siblings, social status, and place of residence. The result of this research is a system that is able to rank the best alternatives as a recommendation in giving scholarships so that the scholarships can be distributed appropriately.